2014
DOI: 10.1063/1.4870710
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk artefacts in Kelvin probe force microscopy imaging: A comprehensive study

Abstract: We provide in this article a comprehensive study of the role of ac cross-talk effects in Kelvin Probe Force Microscopy (KPFM), and their consequences onto KPFM imaging. The dependence of KPFM signals upon internal parameters such as the cantilever excitation frequency and the projection angle of the KPFM feedback loop is reviewed, and compared with an analytical model. We show that ac cross-talks affect the measured KPFM signals as a function of the tip-substrate distance, and thus hamper the measurement of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 15 publications
(6 reference statements)
1
59
0
Order By: Relevance
“…It has been shown that AM-KPFM is susceptible to internal AC-signal couplings which can lead to a topography-dependent offset in the applied voltage. [ 68 ] Thus, to ensure no topography pick up we measure the cantilever response to electrostatic excitation in both the in-and out-of-phase channels across the entire resonance. The response is that of a simple harmonic oscillator, without any sign of AC coupling.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that AM-KPFM is susceptible to internal AC-signal couplings which can lead to a topography-dependent offset in the applied voltage. [ 68 ] Thus, to ensure no topography pick up we measure the cantilever response to electrostatic excitation in both the in-and out-of-phase channels across the entire resonance. The response is that of a simple harmonic oscillator, without any sign of AC coupling.…”
Section: Methodsmentioning
confidence: 99%
“…nonlocal cantilever contributions), since these contributions are subtracted. It should be noted, that the intrinsic capacitance gradient is still dependent on the sample geometry and dimensions since they determine the overall electric polarization of the sample, and hence, the force acting on the tip [31][32][33][34]. Experimentally the topographic crosstalk capacitance gradient image can be constructed following the procedure that we applied for the case of capacitance measurements in Ref.…”
Section: Topographic Crosstalk In Lift-mode Efmmentioning
confidence: 99%
“…As a consequence, the tip-substrate distance varies during the image acquisition, thus inducing spurious capacitance variations that are not related to the dielectric properties of the sample. That is, dielectric images of non-planar samples can be severely affected by topographic crosstalks [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…These include Kelvin probe force microscopy, 225,226 electroluminescence measurements, UV-visible spectrometry for bandgap determination, and time-resolved photoluminescence spectroscopy, as detailed in the introduction, with additional useful explanations in the PES section. For example, time-resolved photoluminescence measurements often show single crystals to have a fast initial decay, followed by a slower decay.…”
Section: Chemistry Of Materialsmentioning
confidence: 99%